PENGARUH LATIHAN MEDICINE BALL THROW TERHADAP POWER OTOT LENGAN DAN BAHU PADA CLUB BOLA VOLI PUTRA H2R KOTA PEKANBARU - Sidik Triwibiksono; Zainur Zainur; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The problem in this research is that it is still very lacking when hitting the ball and the speed of the ball is very low, so it is easily accepted by opponents without checkers or blockers, besides that the hand swing is still very flawed. less quickly, every time some athletes find themselves hitting the ball. often late and the ball is low out of the net before it is hit. The aim of this research was to determine the drug for ball throwing exercises with arm and shoulder muscle strength. The population in this research was the Pekanbaru H2R volleyball club, a total of 10 samples using the total sampling technique. This instrument is a madicine bullet test. Data analysis using t-distribution test. Based on the results of the normality test, variable (X) gets LoMax of 0.199 and variable (Y) gets LoMax of 0.119 compared to Ltable of 0.258, so the assumption is normal. Based on the analysis performed, the value between the initial test and the final test with a significant level of 0.05 indicates that the value (6.285) (1.833) It is thus stated that there is an effect of madicine ball throwing exercises on the arm and shoulder muscle strength in the Pekanbaru H2R volleyball club.Key Words: Volleyball, Medicine Ball Thraw Exercise, Arm and Shoulder Muscle Strength